Project Owner Toxic Leadership: Implications for a Dual Metro Project in UP, India - Prof Dr Paul James (Journal of Management Research, 2024)
This study is focused on the opinions of PMC/Engineer staff of a dual metro in India in relation to the level, causes and implications for toxic leadership, utilised by the Employer of a multibillion dollar, dual metro project, in India. A qualitative/interpretive methodology was employed using grounded theory to enable an understanding of the views and practices concerning the Employer performance and project management capability. The research scope were authoritive opinions from PMC/Engineer staff - a major stakeholder entity contracted by the Employer to oversee the project construction. The population focus was made up of seventeen (17) key-personnel respondents, from a Project Management JV, located across two (dual) metro construction projects. The research outcomes comprised of five (5) main-themes - Employer Management, Technical Outcomes, Works Features, Contract Issues, and Public Stance; and the corresponding eighteen sub-themes (18) - with 327 discussion targets. The research raised a variety of important issues associated with the toxic leadership and performance of the Employer and project management competence, where inadequate and biased Employer performance mechanisms, has forced dismissals, created incoherent performance outcomes, arrogation of the PMC contract through manipulation, harassment and bullying that formed the basis for inadequate decision-making by the Employer for personal gain - leading to unsafe underground works and stations used by members of the public.